ABCA3 mutations in adult pulmonary fibrosis patients: a case series and review of literature. Issue 3 (May 2020) - Klay, Dymph; Platenburg, Mark G.J.P.; van Rijswijk, Rein H.N.A.J.; Grutters, Jan C.; van Moorsel, Coline H.M.
Abstract : Purpose of review: The current review aims to recognize the variability in clinical presentation of adult patients with bi-allelic ABCA3 mutations, create more depth in ABCA3 mutations reported and highlight the influence of environmental factors on disease course. Recent findings: Mutations in ABCA3 are predominantly linked to neonatal and pediatric interstitial lung disease (ILD) with a minority surviving beyond puberty. Here, we present three patients with ABCA3 mutations who present with disease at the age of 19, 61 and 77. Moreover, we identified c.4451G>C (p.R1484P), c.1675G>A (p.G559R) and c.4745C>G (p.T1582S) as three novel ABCA3 mutations. In addition, we identified six additional patients with ABCA3 mutations in literature who reached an age above 18. Furthermore, we discuss the influence of infections, drugs and smoking on disease course. Summary: Although extremely rare, patients with bi-allelic mutations in ABCA3 may present at adulthood. Late onset of disease may be influenced by type of mutation or environmental factors.